2007
DOI: 10.1007/s10856-007-3158-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of open-cell foam synthetic thoracic vertebrae

Abstract: This study presents comprehensive morphological and mechanical properties (static, dynamic) of open-cell rigid foams (Pacific Research Laboratories Inc. Vashon, WA) and a synthetic vertebral body derived from each of the foams. Synthetic vertebrae were comprised of a cylindrical open-cell foam core enclosed by a fiberglass resin cortex. The open-cell rigid foam was shown to have similar morphology and porosity as human vertebral cancellous bone, and exhibited a crush or fracture consolidation band typical of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…Previous studies have primarily relied on uniaxial testing to characterise elastic properties of trabecular bone (Goldstein, 1987;Røhl et al, 1991;Kopperdahl and Keaveny, 1998) and PU trabecular bone analogue (Thompson et al, 2003;Johnson and Keller, 2008;Patel et al, 2008;Calvert et al, 2010). In terms of elastic properties, the mean Young's modulus of grade 20 cellular PU measured in this study (141.3 MPa) is very close to the value of 137 MPa reported by the manufacturer and in previous studies (Thompson et al, 2003;Patel et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have primarily relied on uniaxial testing to characterise elastic properties of trabecular bone (Goldstein, 1987;Røhl et al, 1991;Kopperdahl and Keaveny, 1998) and PU trabecular bone analogue (Thompson et al, 2003;Johnson and Keller, 2008;Patel et al, 2008;Calvert et al, 2010). In terms of elastic properties, the mean Young's modulus of grade 20 cellular PU measured in this study (141.3 MPa) is very close to the value of 137 MPa reported by the manufacturer and in previous studies (Thompson et al, 2003;Patel et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…Ultimate stress and modulus were found to be inferior to that of biological trabecular bone at 0.26 MPa and 14.4 MPa respectively, consistent with previous studies of synthetic bone models (Johnson and Keller, 2008). This compares to typical ultimate stress values for biological bone of 2.23 MPa with an elastic modulus of 291 MPa (Kopperdahl and Keaveny, 1998), both of which differ by an order of magnitude relative to the synthetic model.…”
Section: Static and Fatigue Propertiessupporting
confidence: 87%
“…Many of these studies utilise an aluminium based open cell structure, which have been found to exhibit favourable properties for the study of cement injection micromechanics in terms of damage evolution and distribution (Guillén et al, 2011). To the author's knowledge only one previous study has examined the fatigue properties of a commercial polyurethane open cell bone model, albeit encapsulated within a fibreglass cortex, and found similar cyclic damage accumulation compared to human vertebral bodies (Johnson and Keller, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…14 The epoxy sheet simulated the dense superior endplate of the vertebra. Initially 20-mm wide ϫ 20-mm deep cross-section blocks were used.…”
Section: Methodsmentioning
confidence: 99%